Aggressive angiomyxoma vulva - Jayaram, Surya; Mayadevi, Sarojini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Aggressive angiomyxoma is a mesenchymal tumour which is locally invasive and seen in women of reproductive age group. We present a case of 46-year-old post hysterectomy lady with swelling in left side of vulva.